Numerical Simulation to Study the Effects of Riemann Problems on the Physical Properties of the Astrophysics Gas Dynamics - Al-Mashhadani, L. Y. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this work we run simulation of gas dynamic problems to study the effects of Riemann problems on the physical properties for this gas. We studied a normal shock wave travels at a high speed through a medium (shock tube). This would cause discontinuous change in the characteristics of the medium, such as rapid rise in velocity, pressure, and density of the flow. When a shock wave passes through the medium, the total energy is preserved but the energy which can be extracted as work decreases and entropy increases.The shock tube is initially divided into a driver and a driven section by a diaphragm. The shock wave is created by increasing the pressure in the driver section until the diaphragm bursts, sending normal shock waves down the shock tube into the low pressure driven section and at the same time sending an expansion wave into the high pressure driver section.